The Comparative Analysis of a Novel Acetabular Component against Hemispherical Component in Case of Extensive Acetabular Bone Defects — A Study of Finite Element Analysis. (8th February 2013) - Ma, Wenhui; Zhang, Xuemin; Zhang, Yingze
The purpose of this study was to evaluate the design of a cup using finite element method and to analyze possible effects of joint loading postoperatively, and its initial mechanical stability, so as to direct its further optimization. Finite-element (FE) models of the cup with three wings and the hemispherical cup were created to calculate the stress patterns during a normal gait cycle. The stress in the acetabular components were analyzed and compared. The FE analysis demonstrated that all kinds of acetabular components had the same trend for stress and strain. The stress of the wings increased gradually from rim to root. Its peak stress was significantly lower than the yield force of the Co-Cr-Mo alloy at the joint between the wing and the shell. The graft portion near the acetabular component was subjected to higher stress conditions. The contact stresses were found to be decreased with a reduced abduction angle of wings. The cup with wings of abduction angle of 15° had lower stresses compared with other cups. The cup with wings is a reliable option for the reconstruction of the acetabulum with extensive bone socket defects. The reduced abduction angle of wings helps to decrease the stress of the cup with wings. The FE analysis is a useful tool with which to address these issues.